Fandom and Generative Artificial Intelligence: Heteronormativity and Dissidences in Harry Potter and Twilight - de la Torre Espinosa, Mario; Blázquez Jordán, Jose Manuel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Fandom has created alternative narratives and images to extend literary works, films and video games, thereby fostering a participatory transmediality as advocated by Robert Pratten. It allows users to develop suggested or non-existent plots, including romantic relationships between characters, ranging from the heteronormative to the homoerotic. With generative artificial intelligence, this phenomenon continues, especially in cases such as Harry Potter and Twilight, where the realism achieved by this technology brings creative innovations that enrich the original stories.